Plan Estratégico de Marketing en la Industria Alimenticia Imperial. - Cabello Martínez, Miguel Ángel (2020)
The case study presented below was carried out in the Imperial Food Industry located in the canton Alfredo Baquerizo Moreno (Jujan) at km 53 of the Babahoyo-Duran highway, which seeks to establish a strategic marketing plan to improve Sales levels and market positioning. The Imperial Food Industry has as its main function the purchase of husk and pile rice and the sale of processed rice as aged long grain rice for the coast and the mountains, the commercialization of rice derivatives such as rice, powder and rice flour . The Imperial Industry has as its main problem the inefficient use of a strategic marketing plan that allows it to obtain the appropriate market positioning. By not using as a priority tool the use of advertising strategies to inform about the diversity of rice offered and their respective prices, consumers do not put the respective care at the time of purchase, due to lack of knowledge about the quality or qualities of the product Therefore, they end up buying products offered by direct competitors to the Industry.